2022
DOI: 10.1021/acs.nanolett.2c00739
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Zero-Phonon Line of the Boron Vacancy Center by Cavity-Enhanced Emission

Abstract: Negatively charged boron vacancies (V B –) in hexagonal boron nitride (hBN) exhibit a broad emission spectrum due to strong electron–phonon coupling and Jahn–Teller mixing of electronic states. As such, the direct measurement of the zero-phonon line (ZPL) of V B – has remained elusive. Here, we measure the room-temperature ZPL wavelength to be 773 ± 2 nm by coupling the hBN layer to the high-Q nanobeam cavity. As the wavelength of cavity mode is tuned, we observe a pronounced intensity resonance, indicating th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Experiments have shown that the V B − defect a packet spectrum peaked at ∼810 nm and zero-phonon line (ZPL) is not observed even at low temperature. 24 Recently, some researchers have shown that the ZPL of V B − is at 773 nm through Purcell enhancement from the photonic crystal cavity, 28 which is consistent with the theoretical results. 29 The electron spin orientation of the V B − defect is out-of-plane relative to the lattice of hBN, and the dipole source orientation of the V B − defect is in-plane.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Experiments have shown that the V B − defect a packet spectrum peaked at ∼810 nm and zero-phonon line (ZPL) is not observed even at low temperature. 24 Recently, some researchers have shown that the ZPL of V B − is at 773 nm through Purcell enhancement from the photonic crystal cavity, 28 which is consistent with the theoretical results. 29 The electron spin orientation of the V B − defect is out-of-plane relative to the lattice of hBN, and the dipole source orientation of the V B − defect is in-plane.…”
Section: Introductionsupporting
confidence: 76%
“…46 Furthermore, the efficiency of microwave radiation is limited using some of these methods, resulting in low optically detected magnetic resonance (ODMR) contrast. 28,30…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, numerous efforts have been directed toward integrating 2D materials with SiN nanophotonic devices and plasmonic nanocavities to control their radiative properties. The typical scheme for coupling 2D light sources to a nanophotonic structure is to prefabricate a nanostructure and transfer the 2D material onto it .…”
mentioning
confidence: 99%
“…The hBN nanocavities enable the study of spin qubits in hBN, such as the boron vacancy center. , These qubits exhibit weak optical transitions, making it difficult to observe single or few emitters as opposed to large ensembles. Enhancing emitter-photon coupling via nanophotonic cavities will pave the way for single-qubit control, enabling applications in quantum sensing and quantum information processing.…”
mentioning
confidence: 99%
“…16–20 However, the photoluminescence emission from V B − spans in the NIR has no clear indication of zero phonon line (ZPL) even at cryogenic temperature, and the exact electronic level structure and emission dipole of V B − are yet to be understood. Just recently, coupling of the defects into high-quality cavities suggests the ZPL spectral location to be around 770 nm 21 and excited state spectroscopy of the defects revealed the spin states in the excited state. 22–24 Moreover, the defect suffers from low intrinsic brightness and quantum efficiency.…”
mentioning
confidence: 99%